2002
DOI: 10.1046/j.1528-1157.2002.37801.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Changes and ECG Abnormalities During Epileptic Seizures: Prevalence and Definition of an Objective Clinical Sign

Abstract: Summary:Purpose: To determine the prevalence of heart rate changes and ECG abnormalities during epileptic seizures and to determine the timing of heart rate changes compared to the first electrographic and clinical signs. To assess the risk factors for the occurrence of ECG abnormalities.Methods: We analyzed retrospectively 281 seizures in 81 patients with intractable epilepsy who had prolonged video-EEG and two-channel ECG. The nature and timing of heart rate changes compared to the electrographic and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
218
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(247 citation statements)
references
References 27 publications
14
218
0
8
Order By: Relevance
“…16 Severe tachycardia, a common feature of seizures in human patients, correlates with neuronal discharges and is a sensitive method for early detection of seizures in newborns and adult patients. [20][21][22][23][24] In newborn piglets, we observed a robust increase in HR concomitant with vasodilation of pial arterioles for the duration of the ictal episode. 7-10 Therefore, we compared the bicuculline-induced dynamics of HR as a reliable indicator of seizure activity in control and CORM-A1-treated piglets (Figure 3).…”
Section: Acute Effects Of Enteral Corm-a1 In Systemic and Cerebral CImentioning
confidence: 69%
See 1 more Smart Citation
“…16 Severe tachycardia, a common feature of seizures in human patients, correlates with neuronal discharges and is a sensitive method for early detection of seizures in newborns and adult patients. [20][21][22][23][24] In newborn piglets, we observed a robust increase in HR concomitant with vasodilation of pial arterioles for the duration of the ictal episode. 7-10 Therefore, we compared the bicuculline-induced dynamics of HR as a reliable indicator of seizure activity in control and CORM-A1-treated piglets (Figure 3).…”
Section: Acute Effects Of Enteral Corm-a1 In Systemic and Cerebral CImentioning
confidence: 69%
“…8 Alternatively, one may hypothesize that CO-derived CORM-A1 has anticonvulsant effects. However, CORM-A1 did not affect the dynamics of ictal tachycardia, a reliable and sensitive indicator of status epilepticus in patients, [20][21][22][23][24] of the EEG suggested that CO has proconvulsant, rather than anticonvulsant action. 16 Importantly, CORM-A1 (2 mg/kg), administered via enteral or parenteral routes, provides a safe and effective pharmacological option for prevention of oxidative stress-induced cerebral vascular disease.…”
Section: Discussionmentioning
confidence: 91%
“…In turn, ictal bradycardia (IB) is generally believed to be rare 2,4 . The reported prevalence varies according to bradycardia definition 2,4,5 . However, in a recent prospective study of 19 individuals with intractable seizures, up to 21% exhibited severe bradycardia or asystole requiring permanent pacemaker (PM) 3 .…”
mentioning
confidence: 99%
“…Cardiac rhythm recorded 20-30 sec before each seizure onset was compared with cardiac rhythm recorded 10 sec after the onset of seizure. The definition of ictal bradycardia varies in the literature [3][4][5] . We chose to define absolute IB as a cardiac rhythm less than 60beats per minute (bpm) with a fall of more than 30 bpm, severe IB if heart rate (HR) fell below 42 bpm and relative IB as less striking decreases of HR (exceeding 10 bpm) and HR below 80 bpm.…”
mentioning
confidence: 99%
“…Marshal et al 7 avaliaram 12 pacientes que foram monitorados por meio de video-EEG e ECG, simultaneamente, observando a ocorrência de taquicardia durante as crises epilépticas. Paralelamente, Zijlmans et al 8 observaram que ocorre um aumento na freqüência cardíaca de pelo menos 10 batimentos por minuto imediatamente antes do início das crises em 93% dos pacientes e em 23% das crises (49% dos pacientes), a taquicardia precedeu o início clínico e eletrográfico das crises.…”
unclassified